Genome‐wide association of functional traits linked with Campylobacter jejuni survival from farm to fork. (25th January 2017) - Yahara, Koji; Méric, Guillaume; Taylor, Aidan J.; de Vries, Stefan P. W.; Murray, Susan; Pascoe, Ben; Mageiros, Leonardos; Torralbo, Alicia; Vidal, Ana; Ridley, Anne; Komukai, Sho; Wimalarathna, Helen; et al.
Summary: Campylobacter jejuni is a major cause of bacterial gastroenteritis worldwide, primarily associated with the consumption of contaminated poultry. C. jejuni lineages vary in host range and prevalence in human infection, suggesting differences in survival throughout the poultry processing chain. From 7343 MLST‐characterised isolates, we sequenced 600 C. jejuni and C. coli isolates from various stages of poultry processing and clinical cases. A genome‐wide association study (GWAS) in C. jejuni ST‐21 and ST‐45 complexes identified genetic elements over‐represented in clinical isolates that increased in frequency throughout the poultry processing chain. Disease‐associated SNPs were distinct in these complexes, sometimes organised in haplotype blocks. The function of genes containing associated elements was investigated, demonstrating roles for cj1377c in formate metabolism, nuoK in aerobic survival and oxidative respiration, and cj1368‐70 in nucleotide salvage. This work demonstrates the utility of GWAS for investigating transmission in natural zoonotic pathogen populations and provides evidence that major C. jejuni lineages have distinct genotypes associated with survival, within the host specific niche, from farm to fork.